2019
DOI: 10.1186/s12935-019-1047-z
|View full text |Cite
|
Sign up to set email alerts
|

SKA1 promotes malignant phenotype and progression of glioma via multiple signaling pathways

Abstract: BackgroundSpindle and kinetochore associated protein 1 (SKA1) is a protein involved in chromosome congression and mitosis. It has been found to be upregulated and oncogenic in several human cancers. Herein, we investigated the precise role of SKA1 in the progression and malignant phenotype of human glioma.MethodsBioinformatic analysis was carried out based on the RNA-seq data and corresponding clinical data from GEO, TCGA and CGGA databases. Western blot was performed to analyze the expression of SKA1 in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…40 Knockdown of SKA1 repressed the ability of cell proliferation, migration and invasion of PCa 41 and glioma. 40 SKA2 expression was also increased in breast cancer tissues and cells, and associated with lymph node metastasis. SKA2 knockdown significantly reduced the migration and invasion by reversing EMT.…”
Section: Discussionmentioning
confidence: 98%
“…40 Knockdown of SKA1 repressed the ability of cell proliferation, migration and invasion of PCa 41 and glioma. 40 SKA2 expression was also increased in breast cancer tissues and cells, and associated with lymph node metastasis. SKA2 knockdown significantly reduced the migration and invasion by reversing EMT.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have reported that SKA1 promotes cancer progression in a variety of tumors (13,19,(57)(58)(59)(60)(61). An in vitro study found that SKA1 accelerates cell proliferation and cancer progression in glioma via tumor-associated signaling pathways, including cell cycle and Wnt/β-catenin signaling (62). An immunohistochemical study of 126 hepatocellular carcinoma patients revealed that SKA1 expression is significantly elevated in tumor tissues, and it can regulate the hepatocellular carcinoma cell cycle and contributes to poor prognosis (63).…”
Section: Discussionmentioning
confidence: 99%
“…SKA1 has been proven to accelerate tumorigenesis through the activation of several signaling pathways [ 22 ]. Herein, Gene Set Enrichment Analysis (GSEA) indicated that Notch and Wnt signaling pathways were both positively associated with SKA1 expression in BC ( Figure 6a ).…”
Section: Resultsmentioning
confidence: 99%